A new ambipolar copolymer for organic electronics. Issue 1 (2nd January 2018) - Wu, Xinwei; Sun, Cheng; Song, Hyeng gun; Kim, Yun-Hi
ABSTRACT: The 5-(heptadecan-9-yl)dithieno[3, 2-b:2′, 3′-d]pyridine (NET) structure was designed as a new donor unit for copolymer synthesis. Benzothiadiazole (BT) was used as the electron acceptor unit. The new donor–acceptor copolymer was obtained through the Stille coupling reaction. The density functional theory analysis of the new copolymer showed that the highest occupied molecular orbital electron density was localized on the NET unit while the lowest unoccupied molecular orbital electron density was localized partially on the BT and partially on the pyridine group of the NET unit. The polymer presented good solubility and thermal stability, which are desirable properties for use in solution-processed devices. The new polymer is expected to show a potential for application in organic electronics, such as thin-film transistors.